Luminescence efficiency of cerium-doped yttrium aluminum garnet ceramics formed by radiation assisted synthesis - Alpyssova, G.; Lisitsyn, L.; Golkovski, M.; Mussakhanov, D.; Karipbayev, Zh.; Grechkina, T.; Karabekova, D.; Kozlovskiy, A. (Eastern-European Journal of Enterprise Technologies, 2021)
The variety of applications of yttriumaluminum garnet (YAG)-based luminescent materials and the morphology necessary for these purposes required the development of many technologies for their synthesis. All synthesis technologies used are complex. The structural phase of yttrium-aluminum garnet is formed with any technology, at temperatures exceeding 1.500 °C. The starting materials for the synthesis are metal oxides of aluminum, yttrium and other oxides for activation and modification. It seems possible to use hard radiation to form a new phase. Radiation synthesis of ceramics is realized in less than 1 s, without the use of any additives and influences. The synthesis was carried out at the electron accelerator of the Institute of Nuclear Physics (Novosibirsk). In this work, we studied the spectral-kinetic and quantitative characteristics of luminescence for the first time obtained by the method of radiation synthesis of ceramic samples of yttrium-aluminum garnet doped with cerium with statistical processing of their values. The dependences of the reproducibility of the spectral characteristics of the luminescence of the samples on the preliminary preparation of the charge for synthesis have been investigated. Several cycles of luminophore brightness studies have been performed. It is shown that the obtained ceramics based on yttrium-aluminum garnet doped with cerium possesses the required spectral-kinetic properties, and the efficiency of conversion of the chip radiation into luminescence is achieved, which is comparable to that available in commercial phosphors. The maximum measured values of the position of the bands are from 553.5 to 559.6 nm. Brightness values range from 4.720 to 1.960 cd/m2. It was found that the main reason for the scatter in the characteristics of the luminescent properties of ceramics of yttriumaluminum garnet, activated by cerium obtained by radiation assisted synthesis is the high rate of synthesis and, especially, the high rate of cooling of the samples
Keywords: white LEDs (light-emitting diode); yttrium-aluminum garnet; phosphors; luminescence; synthesis in the radiation field